A nutritional intervention programme at a worksite canteen to promote a healthful lifestyle inspired by the traditional Mediterranean diet. (2nd January 2018) - Vitale, Marilena; Bianchi, Marta A.; Rapetti, Valeria; Pepe, Josè M.; Giacco, Angela; Giacco, Rosalba; Riccardi, Gabriele
Abstract: This study investigates the effectiveness and long-term impact on the composition of the habitual diet of a nutritional intervention programme – undertaken through panels, totems, and table mats or handout leaflets – based on the promotion at a worksite canteen of healthy food-choices resembling the traditional Mediterranean diet. A significantly higher choice of dishes based on wholegrain cereals, legumes, white meat and fish, and a lower choice of dishes based on refined cereals, red and processed meat, eggs and cheese was observed at the end of the intervention and after six months and three years of follow-ups. A significantly better adherence to the nutritional recommendations for saturated-fat, cholesterol, sugars and fibre was observed. This study reveals that a nutritional intervention programme promoting the traditional Mediterranean diet and utilising a minimally intensive approach is feasible and effective to modify in a beneficial way the dietary habits of a working population and keep these changes in the long-term.